Enhancement of critical-sized bone defect regeneration by magnesium oxide-reinforced 3D scaffold with improved osteogenic and angiogenic properties. (1st February 2023) - Chen, Bo; Lin, Zhengjie; Saiding, Qimanguli; Huang, Yongcan; Sun, Yi; Zhai, Xinyun; Ning, Ziyu; Liang, Hai; Qiao, Wei; Yu, Bingsheng; Yeung, Kelvin W.K.; Shen, Jie
Highlights: 3D bio-nanocomposite scaffold which have an ideal magnesium ionic microenvironment was developed for critical-sized bony tissue repairing. Significantly enhanced osteogenic effects were observed over the bio-nanocomposite as compare to the polycaprolactone control. The rodent femoral and critical-sized cranial defect models were applied to characterize the osteogenesis in vivo . Magnesium enriched scaffold exhibited remarkably increased bone volume, enhanced angiogenesis, and almost recovered critical-sized defect after an 8-week implantation. Abstract: The healing of critical-sized bone defects (CSD) remains a challenge in orthopedic medicine. In recent years, scaffolds with sophisticated microstructures fabricated by the emerging three-dimensional (3D) printing technology have lighted up the treatment of the CSD due to the elaborate microenvironments and support they may build. Here, we established a magnesium oxide-reinforced 3D-printed biocomposite scaffold to investigate the effect of magnesium-enriched 3D microenvironment on CSD repairing. The composite was prepared using a biodegradable polymer matrix, polycaprolactone (PCL), and the dispersion phase, magnesium oxide (MgO). With the appropriate surface treatment by saline coupling agent, the MgO dispersed homogeneously in the polymer matrix, leading to enhanced mechanical performance and steady release of magnesium ion (Mg 2+ ) for superior cytocompatibility, higher cell viability, advanced osteogenic differentiation, and cell mineralization capabilities in comparison with the pure PCL. The in-vivo femoral implantation and critical-sized cranial bone defect studies demonstrated the importance of the 3D magnesium microenvironment, as a scaffold that released appropriate Mg 2+ exhibited remarkably increased bone volume, enhanced angiogenesis, and almost recovered CSD after 8-week implantation. Overall, this study suggests that the magnesium-enriched 3D scaffold is a potential candidate for the treatment of CSD in a cell-free therapeutic approach. Graphical abstract: Image, graphical abstract